2005
DOI: 10.4049/jimmunol.175.9.5586
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TRAIL Deficiency Accelerates Hematological Malignancies

Abstract: TNF apoptosis-inducing ligand is attracting considerable interest as a potential extrinsic tumor suppressor mechanism, although previous reports have conveyed somewhat contrasting views regarding the likely importance of this pathway. In this study, we provide the first evaluation of spontaneous tumor formation over the life span of TRAIL-deficient mice. Interestingly, >25% of these mice do develop lymphoid malignancies after 500 days of life. TRAIL suppressed the initiation and development of both tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 24 publications
3
123
0
1
Order By: Relevance
“…4T1.2, NIH 3T3, and P815 cells have been described (19). ErbB-2/neuT tumor lines were generated as described (34). Briefly, lobular breast carcinomas were excised from 20-to 23-week-old female BALB/c MMTV-ErbB-2/neuT transgenic mice and digested with DNase I and collagenase.…”
Section: Methodsmentioning
confidence: 99%
“…4T1.2, NIH 3T3, and P815 cells have been described (19). ErbB-2/neuT tumor lines were generated as described (34). Briefly, lobular breast carcinomas were excised from 20-to 23-week-old female BALB/c MMTV-ErbB-2/neuT transgenic mice and digested with DNase I and collagenase.…”
Section: Methodsmentioning
confidence: 99%
“…Both TRAILand TRAIL receptor-deficient animals display increased susceptibility to tumor metastasis [10,11]. It has been reported that TRAIL deficiency leads to autoimmune disease progression, as well as to defects in thymocyte negative selection, although the latter finding is controversial [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…The pivotal role of TRAIL in tumor defense is underlined by the observation that TRAIL-deficient mice are more susceptible to chemically induced as well as spontaneous tumors. [11][12][13] TRAIL-R1/2 expression in healthy cells, including hepatocytes and quiescent stellate cells, is absent or relatively low and often cytoplasmic, instead of membrane bound. [14][15][16] In contrast, in numerous cancers, including HCC, TRAIL-R1/2 protein expression is highly up-regulated.…”
mentioning
confidence: 99%